Digital knowledge translation tools for sexual and reproductive health information to adolescents: an evidence gap-map - Meherali, Salima; Hussain, Amber; Rahim, Komal Abdul; Idrees, Sobia; Bhaumik, Soumyadeep; Kennedy, Megan; Lassi, Zohra S. (Therapeutic advances in reproductive health, 2024)
Background: Digital knowledge translation (KT) interventions play a crucial role in advancing adolescent sexual and reproductive health (ASRH). Despite the extensive literature on their effectiveness, there’s a lack of synthesized evidence on the efficacy of digital KT tools for adolescent ASRH globally. Objectives: This review aimed to systematically identify and map existing empirical evidence on digital KT tools targeting ASRH outcomes and identify research gaps. Design: The review employed an evidence gap-map (EGM) approach following 2020 PRISMA reporting guidelines. Data sources and methods: A comprehensive literature search was conducted across databases including Medline, EMBASE, Global Health, CINAHL, Scopus, and Cochrane. Covidence software was used for data management. EPPI-Mapper software was used to synthesize findings and develop a graphical EGM. Results: The EGM comprises 68 studies: 59 experimental and 9 systematic reviews, predominantly from African (19 studies) and American regions (22 studies), with limited research from the Eastern Mediterranean and South East Asian regions. It examines digital KT tools’ influence on sexual and reproductive health (SRH) outcomes, identifying research gaps. Websites are extensively studied for their impact on adolescent behavior, knowledge, attitude, and self-efficacy, yet research on their effects on ASRH and health services access is limited. Similarly, mobile apps and short message service (SMS)/text messages impact various aspects of SRH outcomes, but research on their effects on health services utilization is insufficient. Interventions like digital pamphlets and gaming lack exploration in health service access. OTT media and social media need further investigation. Mass media, including radio, television, and podcasts, are largely unexplored in adolescent SRH outcomes. Topics such as menstrual hygiene, abortion, and sexual and intimate partner violence also lack research. Conclusion: The review underscores the dominance of certain KT tool interventions like SMS and websites. Despite advancements, research gaps persist in exploring diverse digital platforms on underrepresented outcomes globally. Future research should expand exploration across digital platforms and broaden the scope of outcome measures. Trial registration: The protocol is registered with PROSPERO (CRD42022373970).